Disain dan Analisa Rangka Belt Conveyor Pemilah Manual Kapasitas 8 Ton m3/jam - Aranda, Irwan (Universitas Pamulang, 2024)
A manual sorting conveyor belt is a machine that functions to move raw materials from one place to another and sort the raw materials conventionally. To make a manual sorting belt conveyor machine, a construction is needed, namely a frame that functions as a support to support all components such as the belt, roller, hopper, output and gravity roller conveyor. The frame material to be used must have mechanical properties that are sturdy, strong and resistant to vibrations in the machine when operated. To obtain maximum value in designing a conveyor belt machine, a planning concept is needed according to the needs and materials to be used. In this research, design and analysis were carried out using Solidworks 2020 software with ASTM A36 Steel material with an accepted static load of 81340 N from the component weight. The results obtained in the design include the design of the conveyor belt frame. The simulation results with a load of 81340 N were obtained from the Von misses simulation on the conveyor frame resulting in a max value of 5.27 N/mm² and a min of -36.72 N/mm² with a deformation scale of 10, Analysis of the displacement simulation on the conveyor frame with a load of 81340 N produces a max value of 10.25 mm and a min of 0.00 mm with a deformation scale of 10. Analysis of the safety factor simulation on the conveyor frame with a load of 81340 N produces a max value of 8.65 x 106 and min 1.5 so that the manual sorting belt conveyor machine design is declared safe to use. The comparison between the simulation results and the calculation results has an error percentage including von Mises stress of 2%, Displementation of 7%, and Safety Factor of 6% so that the simulation and calculation results are declared accurate.